Knowledge and beliefs of parents of asthmatic children presenting to the outpatient department in Kovai medical centre and hospital, Tamil Nadu, India - ., Rajendran; Aarthi, P. (International Journal of Contemporary Pediatrics, 2019)
Background: Childhood asthma has a major impact on a child’s quality of life and that of their parents. To assess the level of understanding and beliefs by parents of asthmatic children about causation, pathophysiology, treatment, and prognosis. Methods: The study was conducted in Kovai medical centre and hospital Coimbatore in 2017. Totally 101 asthmatic children were included in the study. Asthmatic children aged 6 years to 15 years. A total of 101 parents participated in this study. The sex and age of the informant, mother’s literacy and mother’s occupation were noted. The socio-economic status of the family was computed using modified Kuppuswamy scale 2016. Results: In present study among the 101 children, 38.61% are in the school age (5-8 years), 38.61% are in the tweens (9-12 years) and 22.78% are teenagers. 45.54% of the children are from the rural area. Half of the children are experiencing the disease for more than 6 years now, the other half less than 6 years. 5.94% of the parents interviewed were not aware of the diagnosis. 71.29% thought that asthma is a hereditary condition. Conclusions: A wide gap exists between recommendations and the actual practice. Hence by improving parents’ knowledge about asthma, their attitude and practice can be positively affected.